Evaluasi Program Kelas Olimpiade dengan Metode Cipp (Context, Input, Process, Product) di MTs PPMI Assalaam Sukoharjo - Wihdan Jefri Lazuardi Baihaqi El-Haq; Nur Fadhilah Al-Karimah (Scidac Plus, 2023)
The Education Service Program in this case is the Olympic Class, which is one of several excellent programs at MTs PPMI Assalaam Sukoharjo. Every activity in this program can maximize the ability of students in the field of science and motivate them to master and develop the field of science. Every student who takes part in this program is expected to be able to develop scientific potential to compete in cognitive competitions.The process of implementing the Olympic Class at MTs PPMI Assalaam, is very important for evaluation. The appropriate model for carrying out program evaluation is the CIPP evaluation model (context, input, processes, product). The results of the CIPP evaluation will later explain whether this program can be continued or improved for the advancement of the Olympic Class.This research was conducted qualitatively with the aim of obtaining data and analyzing the implementation and program evaluation policies in the relevant places based on the scope of the program evaluation. Data collection was taken by observation, interviews and documents.This research describes that the evaluation of the Olympic Class is divided into four evaluations 1) context evaluation, namely the Olympic class has a goal in the form of a vision and mission and the goal is to jump-start the potential of students who have more abilities in science, social, foreign languages, and technology, 2) input evaluation namely the competence possessed by ustadz and ustadzah in the Olympic class in teaching is very good, while for students they have good types of abilities in learning and understanding lessons, 3) process evaluation, namely the implementation of the Olympic class program goes well according to what has been programmed by the institution, 4 ) product evaluation, namely the achievement of the achievement targets for students obtained in competitions both locally, nationally and internationally have made many results. This study recommends whether the Olympic Class Education service program at MTs PPMI Assalaam Sukoharjo continues or cannot be continued.